Detection of a mecC-positive Staphylococcus saprophyticus from bovine mastitis in Argentina. (September 2017) - Srednik, Mariela E.; Archambault, Marie; Jacques, Mario; Gentilini, Elida R.
Highlights: This study investigate the antibiotic resistance in staphylococci isolated from bovine mastitis in a dairy farm during two different treatments. This study reports one Staphylococcus saprophyticus isolate from bovine mastitis that is resistant to β-lactams and is positive for the mec C gene. This is the first detection of mec C in South America from CNS in bovine mastitis. Abstract: Introduction: Bovine mastitis causes important economic losses in the dairy industry. Coagulase-negative staphylococci (CNS) are a group of bacteria commonly isolated from bovine mastitis and can display resistance to a wide range of antimicrobial agents. Objectives: The objective of this study was to determine staphylococcal resistance towards β-lactam, macrolide and lincosamide antimicrobials in quarters previously treated with third-generation cephalosporin and after lincosamide intramammary therapy. Methods: Sick quarters of eighteen cows from Villaguay, Entre Ríos (Argentina) with clinical mastitis were studied. All staphylococcal isolates were tested by disk diffusion for their antimicrobial susceptibilities. Cefoxitin resistance was investigated by PCR and sequencing for both the mec A and mec C genes. Results: Resistances to penicillin, oxacillin and cefoxitin were observed, whereas no resistance to macrolide and lincosamide was detected. A cefoxitin-resistant Staphylococcus saprophyticus was found to be mec A-negative but mec C-positive. Conclusions: This study reports for the first time the mec C gene from a CNS in bovine mastitis in South America. Because CNS may act as reservoirs of antimicrobial resistance genes, they can be seen as a potential public health threat with respect to antimicrobial resistance and the development of multiple resistance. Also, the emergence of methicillin-resistant phenotypes will limit therapeutic options.